Structural, Electronic and Magnetic Properties of Defected Water Adsorbed Single-Layer MoS2 - Neupane, Hari Krishna; Adhikari, Narayan Prasad (Journal of Institute of Science and Technology, 2021)
Water adsorbed in MoS2 (wad-MoS2), 1S atom vacancy defect in wad-MoS2 (1S-wad-MoS2), 2S atoms vacancy defects in wad-MoS2 (2S-wad-MoS2), and 1Mo atom vacancy defect in wad-MoS2 (Mo-wad-MoS2) materials were constructed, and their structural, electronic, and magnetic properties were studied by spin-polarized density functional theory (DFT) based first-principles calculations. The wad-MoS2, 1S-wad-MoS2, 2S-wad-MoS2, and Mo-wad-MoS2 materials were found stable. From band structure calculations, wad-MoS2, 1S-wad-MoS2 and 2S-wad-MoS2 materials open energy bandgap of values 1.19 eV, 0.65 eV and 0.38 eV respectively. Also, it was found that the conductivity strength of the material increases with an increase in the concentration of S atom vacancy defects in the structure. On the other hand, the Mo-wad-MoS2 material has metallic properties because energy bands of electrons crossed the Fermi energy level in the band structure. For the investigation of magnetic properties, the density of states (DoS) and partial density of states (PDoS) calculations were used and found that wad-MoS2, 1S-wad-MoS2, and 2S-wad-MoS2 are non-magnetic materials, while Mo-wad-MoS2 is a magnetic material. The total magnetic moment of Mo-wad-MoS2 has a value of 2.66 µB/cell, due to the arrangement of unpaired up-spin and down-spin of electrons in 3s & 3p orbitals of S atoms; and 4p, 4d & 5s orbitals of Mo atoms in the material.